Two new species of Ostracoda from hydrothermal vents of Riftia pachyptila aggregations on the East Pacific Rise (Halocypridina; Cladocopina) - Kornicker, Louis S.; Harrison-Nelson, Elizabeth (Zootaxa, 2005)
Two new species of Ostracoda, Archiconchoecia (Archiconchoecia) chavturi (Halocypridina) and Polycopetta pax (Cladocopina), are described from two diffuse flow vent localities (Tica Site and Riftia Field Site) within Riftia pachyptila (Siboglinidae, Vestimentifera) aggregations on the East Pacific Rise, slightly north and west of 9°50' N, 104°17'W, depth 2500 m.